WHALE SHARK TOURISM AND WELL-BEING: A CASE STUDY OF LABUAN JAMBU - Putrawan Habibi; Muhammad Azizurrohman; Dova Novita (Sekolah Tinggi Pariwisata Mataram, 2021)
As one of the largest whale shark attractions in Indonesia, Labuan Jambu Village still lacks the attention of academics and government in terms of research and development. As a result, it's worth taking a closer look at the people of Labuan Jambu Village's well-being before and after the Whale Shark tourism activities. The authors found that the economic benefits of tourism activities have not had a significant and unequal effect on the villagers. Before the tourism industry existed, the villagers of Labuan Jambu understood the importance of education. Aside from that, the most important problem that Labuan Jambu Village has yet to resolve is waste management. In order to create sustainable tourism in Labuan Jambu Village, various stakeholders must collaborate